Associations of the COVID-19 pandemic with quality of life: A cross-sectional study of older-age people with and without HIV in rural Uganda - Olivieri-Mui, Brianne; Hoeppner, Susanne S; Tong, Yao; Kohrt, Emma; Quach, Lien T; Saylor, Deanna; Seeley, Janet; Tsai, Alexander C; Reynolds, Zahra; Okello, Samson; Asiimwe, Stephen; Flavia, Atwiine; et al. (Journal of Global Health, 2023)
Background: COVID-19-related lock¬downs and other public health mea¬sures may have differentially affected the quality of life (QOL) of older peo¬ple with and without human immuno¬deficiency virus (HIV) in rural Uganda. Methods: The Quality of Life and Ag¬ing with HIV in Rural Uganda study enrolled people with and without HIV aged over 49 from October 2020 to October 2021. We collected data on COVID-19-related stressors (behav¬ior changes, concerns, interruptions in health care, income, and food) and the participants’ QOL. We used linear re¬gression to estimate the associations be-tween COVID-19-related stressors and QOL, adjusting for demographic char¬acteristics, mental and physical health, and time before vs after the lockdown during the second COVID-19 wave in Uganda. Interaction between HIV and COVID-19-related stressors evaluated effect modification. Results: We analysed complete data from 562 participants. Mean age was 58 (standard deviation (SD) = 7); 265 (47%) participants were female, 386 (69%) were married, 279 (50%) had HIV, and 400 (71%) were farmers. Those making ≥5 COVID-19-related behavior changes compared to those making ≤2 had worse general QOL (estimated linear regression coefficient (b) = - 4.77; 95% confidence interval (CI) = -6.61, -2.94) and health-related QOL (b = -4.60; 95% CI = -8.69, -0.51). Having access to sufficient food after the start of the COVID-19 pandemic (b = 3.10, 95% CI = 1.54, 4.66) and being interviewed after the start of the second lockdown (b = 2.79, 95% CI = 1.30, 4.28) were associated with better general QOL. Having HIV was associated with better health-related QOL (b = 5.67, 95% CI = 2.91,8.42). HIV was not associated with, nor did it modify the association of COVID-19-related stressors with general QOL. Conclusions: In the context of the COVID-19 pandemic in an HIV-endemic, low-resource setting, there was reduced QOL among older Ugandans making multiple COVID-19 related behavioral changes. None¬theless, good QOL during the second COVID-19 wave may suggest resilience among older Ugandans
Keywords: COVID-19; Pandemic; Older-age people; HIV; Uganda